2014
DOI: 10.1111/epi.12883
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic excitation of parvalbumin‐positive interneurons contributes to the severity of pilocarpine‐induced seizures

Abstract: SUMMARY Objective A common rodent model in epilepsy research employs the muscarinic acetylcholine receptor (mAChR) agonist pilocarpine, yet the mechanisms underlying the induction of pilocarpine-induced seizures (PISs) remain unclear. Global M1 mAChR (M1R) knockout mice are resistant to PISs, implying that M1R activation disrupts excitation/inhibition balance. Parvalbumin-positive (PV) inhibitory neurons express M1 mAChRs, participate in cholinergically-induced oscillations, and can enter a state of depolariz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 56 publications
2
21
0
Order By: Relevance
“…1) in order to demonstrate that deep-sleep brain states can be controlled by selectively manipulating muscarinic receptors at their physiological location and context. The oscillatory frequency of the network was greatly increased already at 100 nM Iperoxo, and lead to periods of seizure-like discharges, in agreement with previous studies performed by knockout mice and pilocarpine 39,40 in which pathologic activation of muscarinic acetylcholine receptors induced seizures. Photocontrol of muscarinic signaling was subsequently achieved in vitro and in vivo with the photochromic iperoxo derivative PAI, 23 which is targeted allosterically at M2 subtype receptors ( Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…1) in order to demonstrate that deep-sleep brain states can be controlled by selectively manipulating muscarinic receptors at their physiological location and context. The oscillatory frequency of the network was greatly increased already at 100 nM Iperoxo, and lead to periods of seizure-like discharges, in agreement with previous studies performed by knockout mice and pilocarpine 39,40 in which pathologic activation of muscarinic acetylcholine receptors induced seizures. Photocontrol of muscarinic signaling was subsequently achieved in vitro and in vivo with the photochromic iperoxo derivative PAI, 23 which is targeted allosterically at M2 subtype receptors ( Fig.…”
Section: Discussionsupporting
confidence: 91%
“…1B). In addition, at concentrations equal or higher than 100 nM Iperoxo, the oscillatory activity evolved to periods of seizure-like discharges (Fig.1C), 39,40 characterized by low (<1 Hz), delta (1-4 Hz) and alfa (8)(9)(10)(11)(12) Hz) frequencies ( Fig. 1D).…”
Section: Non-specific Activation Of Machrs Evokes Neuronal Hyperexcitmentioning
confidence: 99%
“…Changes of intrinsic excitability in PV fast-spiking cells due to deficits of Nrg1-Erbb4 signaling reported in TLE could also explain our data (Li et al, 2011). Epileptic PV basket cells are particularly susceptible to entering the depolarizing block (Karlócai et al, 2014; Yi et al, 2015), but our intracellular recordings of identified cells suggest that this is not likely to be the case (Fig. 7 H , I ).…”
Section: Discussionmentioning
confidence: 89%
“…The endogenous state that is characterized by theta rhythm is associated with the increased cholinergic activity, seizure severity, and has been found to either promote or prevent a seizure (Colom et al, 2006;Sedigh-Sarvestani et al, 2014;Ewell et al, 2015;Yi et al, 2015).…”
Section: The Emergence Of Theta Rhythms In the Ant During Focal Seizuresmentioning
confidence: 99%